Recent advances in enzymatic biosensors for point‐of‐care detection of biomolecules. Issue 12 (17th October 2022) - Gupta, Upasana; Gupta, Verruchi; Arun, Ravi Kumar; Chanda, Nripen
Abstract: Late state‐of‐the‐art analytical methodologies in chromatography, spectroscopy, and electroanalysis have been developed to meet the challenges of changing environmental and health issues. The modern trends in developing new protocols emphasize economic, portable, nano, or even smaller sample sizes and less time‐consuming processes. This has led to the development of technology‐based biosensors which meet most of the above requirements. The lab‐on‐chip technology exploiting enzyme‐based biosensors has made the analytical processes very efficient, accurate, affordable, and requiring nano‐scale sample sizes. In this review, an attempt is being made to review the literature based on state‐of‐the‐art technology of enzyme‐based biosensors for the detection of biomolecules. Abstract : The schematic representation of a typical enzyme based bio‐sensor, showcasing different elements which include sample analytes extracted from various resources like food, waste, blood and environmental samples etc, which on interaction with specific enzymes immobilized on the transducer surface will undergo interaction and thus detects biomolecules.